Negotiating the (bio)medical gaze – Experiences of trans-specific healthcare in Sweden. (February 2017) - Linander, Ida; Alm, Erika; Hammarström, Anne; Harryson, Lisa
Abstract: In Sweden as well as in other western countries persons with trans experiences have to go through a clinical evaluation in order to get access to gender-confirming medical procedures. The aim of this study is to analyse care-users' experiences of navigating and negotiating access to gender-confirming medical procedures in Sweden. Biomedicalisation is used as a theoretical framework in order to analyse how technoscientific and neoliberal developments are parts of constructing specific experiences within trans-specific care. Constructivist grounded theory was used to analyse 14 interviews with persons having experiences of, or considering seeking, trans-specific healthcare. The participants experienced trans-specific healthcare as difficult to navigate because of waiting times, lack of support, provider ignorance and relationships of dependency between healthcare-users and providers. These barriers pushed the users to take responsibility for the care process themselves, through ordering hormones from abroad, acquiring medical knowledge and finding alternative support. Based on the participants' experiences, it can be argued that the shift of responsibility from care-providers to users is connected to a lack of resources within trans-specific care, to neoliberal developments within the Swedish healthcare system, but also to discourses that frame taking charge of the care process as an indicator that a person is in need of or ready for care. Thus, access to gender-confirming medical procedures is stratified, based on the ability and opportunity to adopt a charge-taking role and on economic and geographic conditions. Based on the results and discussion, we conclude that trans-specific care ought to focus on supporting the care-seekers throughout the medical process, instead of the current focus on verifying the need for care. There is also a need for increased knowledge and financial resources. A separation between legal and medical gender reassignment could contribute to a better relationship between care-providers and care-users and increase the quality of care. Highlights: Fills a knowledge gap by analysing experiences of the Swedish trans-specific care. Care users are forced to be their own project managers in the chain of care. There is a lack of knowledge and financial resources in trans-specific care. Access to gender confirming medical procedures is socially stratified. Trans-specific healthcare must focus on supporting healthcare users.